Management practices in Malaysia in the new economy: A book of readings - Ali, Juhary (Universiti Utara Malaysia Press, 2004)
The book consists of the following topics:i) Management Practices in Malaysia in the New Economy: An Evolution ii) Culture and Leadership Styles iii) Job Redesign in Health Care Sector iv) Knowledge Management in Agile Organisations v) Service Quality in the Malaysian Public Sector vi) Human Resource Management in the Plantation Sector vii) International Management: The Characteristics, Nature and Challenges as Globalisation Rules the Day viii) The Challenges of Globalisation and the Roles of Human Resources Management